Determinants and effects of the learning environment in college classes - Tulloch, Denton (Curtin University, 2011)
This study investigated sex, age, and ethnicity as determinants of classroom environment, as well as the effects of classroom environment on student attitudes at an urban two-year or junior college in Florida, USA. The sample consisted of 544 students in 29 classes that were randomly chosen.The Constructivist Learning Environment Survey (CLES) was used to assess the way in which students perceived their classroom environment, whereas a modified version of the Enjoyment of Science Lessons scale from the Test of Science-Related Attitudes (TOSRA) was used to assess students’ attitudes toward the subject taught in the classes surveyed. Data analyses supported the CLES’s factorial validity, internal consistency reliability, and its ability to differentiate between classrooms when used with adult learners in a post-secondary setting. Similarly, results from analyses conducted on the revised TOSRA scale revealed satisfactory internal consistency reliability.A three-way MANOVA for sex, age and ethnic differences in classroom environment perceptions and enjoyment revealed that: females enjoyed their classes significantly more than did males; students 25 years and older had higher Shared Control and Enjoyment scores, but lower Student Negotiation scores, than did students younger than 25 years; and there were no significant differences between African-Americans and students of other ethnicities for any learning environment scale or for enjoyment. A large effect size of 0.88 standard deviations, suggesting an educationally important sex difference, was found for the attitude scale. However, effect sizes of modest magnitude, ranging from 0.21 to 0.29 standard deviations, were found for age difference.Past research was replicated in that positive and statistically significant bivariate and multivariate associations were found between students’ enjoyment of classes and their perceptions of classroom learning environment. In particular, students enjoyed their classes more when there was a greater emphasis on Shared Control and Student Negotiation. In other words, students responded more positively when they perceived that they had a role to play in the design and management of the learning environment, as well as when opportunities existed for them to explore among their peers the viability of newly developing ideas.Overall, my results suggest that the CLES and the TOSRA are valid and reliable instruments that researchers can use with confidence to measure adult students’ perceptions of learning environment and attitudes, respectively, in the two-year college setting. While no significant sex difference was found for any learning environment scale, females enjoyed their classrooms more than did males. Relative to younger students, older students had higher Student Negotiation and Enjoyment scores. A possible implication is that teachers should make classrooms more appealing and enjoyable to males, while making younger adults feel a greater sense of inclusion in their classrooms.